Epidemiology and video analysis of achilles tendon ruptures in the National Basketball Association - Lemme, N. J.; Li, N. Y.; Kleiner, J. E.; Tan, S.; DeFroda, S. F.; Owens, B. D. (The American Journal of Sports Medicine, 2019)
Background: There is a paucity of literature regarding risk factors and mechanisms of Achilles tendon (AT) ruptures in the National Basketball Association (NBA). Purpose: To identify the risk factors and outcomes of AT ruptures in NBA athletes. Furthermore, using video analysis, to characterize the mechanisms of rupture by identifying the most common playing situations and lower extremity positions at the time of injury. Study Design: Descriptive epidemiology study. Methods: AT ruptures in the NBA that occurred between the seasons of 1969-1970 and 2017-2018 were identified. Player data collected included age, position, body mass index, total games started before and after injury, and Player Efficiency Rating. Injury-related variables collected included date of injury, laterality, minutes played before injury, operative versus nonoperative treatment, and time to return to play. Available video footage was analyzed for the mechanism and body position at the time of injury. Univariable and multivariable linear regression was used to compare changes in performance before and after AT rupture. Statistical significance was set at P < .05. Results: Forty-four ruptures were identified between 1970 and 2018. The mean age was 28.3 years, with players averaging 6.8 seasons before AT rupture. AT ruptures were most prevalent during early-season game play (27.3%), followed by preseason (18.2%) and late season (18.2%). More than a third (36.8%) of players either did not return to play or started in fewer than 10 games in the remainder of their career, with 21% of ruptures leading to retirement. The mean time to return to play was 10.5 months. The Player Efficiency Rating declined by an average of 2.9 points (range, -11.5 to +2.3) (P < .001). Analysis of available injury footage (n = 12) demonstrated all ruptures to be noncontact in nature, most commonly occurring just before takeoff as the player began to push off from a stopped position, with the foot in dorsiflexion, the knee in early flexion, and the hip in extension. Conclusion: In the NBA, a majority of AT ruptures occur early in the season, in veteran players, with almost half not returning to play or starting fewer than 10 games in the remainder of their career. The most common mechanism of injury is taking off from a stopped position just before toe-off in a dorsiflexed foot.